THE EFFECT OF FINANCIAL LITERACY, SUBJECTIVE NORMS, AND PERCEIVED BEHAVIORAL CONTROL ON THE USE OF GOPAY DIGITAL WALLET WITH INTENTION AS A MEDIATION VARIABLE - Arihta Tarigan; Caka Gatot Priambodo; Budi Christanto (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study examines digital payment usage behavior by analyzing the effects of financial literacy, subjective norms, and perceived behavioral control on the intention to use the GoPay digital wallet, as well as the impact of intention on actual usage behavior. Grounded in the Theory of Planned Behavior (TPB), this research adopts a quantitative approach. Data were collected through an online questionnaire distributed via Google Forms to 100 university students and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The findings indicate that financial literacy, subjective norms, and perceived behavioral control significantly influence the intention to use GoPay. In turn, intention has a significant effect on actual usage behavior. Furthermore, intention mediates the relationship between the three antecedent variables and actual usage behavior. These results confirm the applicability of TPB in explaining digital financial behavior, particularly in the context of digital wallet adoption among Generation Z university students, and provide insights for enhancing user engagement strategies in digital financial services. Keywords: Digital Payment Usage Behavior; Financial Literacy; Subjective Norms; Perceived Behavioral Control; Intention; Theory of Planned Behaviour